Determination of acetaldehyde in soil by gas chromatography with a flame ionization detector in combination with static headspace analysis - Larisa P. Nekrasova; Anton V. Sbitnev; Ekaterina I. Filimonova; Oksana Ju. Kuleshova; Maria A. Vodianova (Hygiene and sanitation, 2026)
Introduction. Acetaldehyde is hazardous to the environment, and therefore its content in the air, water and soil is regulated. The maximum permissible concentration in soil is set at 10 mg/kg, but there are no regulatory and methodological documents for its determination in soil.Objective of the study. Determination of acetaldehyde in soil by gas chromatography in combination with static headspace analysis.Materials and methods. The studies were carried out on samples of sod-podzolic, sandy, and urban soils, as well as ordinary chernozem, collected in the Moscow, Kursk, Murmansk, and Tver regions. Acetaldehyde was detected using a hardware and software complex based on a Chromatec-Crystal 5000.2 gas chromatograph (Chromatec, Russia) with a flame ionization detector (FID) and an external Lab Hut HT 200 H-200 equilibrium vapor dispenser (HTA s.r.l., Italy), with a DB-624 capillary column (Agilent, USA) 60 m, 0.53 mm, 3 µm.Results. A large array (more than a thousand) of soil samples was analyzed (list the characteristics of the soils). Acetaldehyde was present in all samples, the concentration of which ranged from 0.04 mg/kg to 6.0 mg/kg. The dependence of the FID signal on the sample mass, its humidity, time, and temperature of thermostatting was studied. The optimal sample mass when using 20 ml vials is 2 g, and the sample humidity for most soil types was found to be 20%. Analysis of soil samples by the EPA 5021 method with the addition of 10 cm3 of a modifying solution or reagent water to 2 g of soil leads to very low values ​​of the chromatographic peak areas, or their absence. Extraction of acetaldehyde directly from the soil sample allows increasing the sensitivity of the detection by 10–60 times.Limitations. Calibration graphs constructed using different types of soils may have different slopes, therefore, for the purpose of unification, it is advisable to use aqueous solutions, although this approach may introduce a systematic error in the analysis results.Conclusion. A method for detecting acetaldehyde in soil using gas chromatography with a flame ionization detector in combination with static headspace analysis has been developed. The detection limit was 0.04 mg/kg.Compliance with ethical standards. The study does not require the conclusion of the Biomedical Ethics Committee.Contribution: Nekrasova L.P. – concept and design of the study, conducting experimental studies, writing the text, collecting material and processing data, editing; Sbitnev A.V. – conducting experimental studies, collecting material and processing data; Filimonova E.I. – conducting experimental studies, processing results, statistical processing; Kuleshova O.Yu. – conducting experimental studies, collecting material and processing data; Vodianova M.A. – collection of material, processing of results. All authors are responsible for the integrity of all parts of the manuscript and approval of the manuscript final version.Conflict of interest. The authors declare no conflict of interest.Funding. The study had no sponsorship.Received: September 18, 2025 / Revised: October 10, 2025 / Accepted: December 2, 2025 / Published: January 15, 2026